Pressurized Liquid Extraction as a Novel Technique for the Isolation of Laurus nobilis L. Leaf Polyphenols - Erika Dobroslavić; Ivona Elez Garofulić; Jelena Šeparović; Zoran Zorić; Sandra Pedisić; Verica Dragović-Uzelac (Molecules, 2022)
Laurus nobilis L., known as laurel or bay leaf, is a Mediterranean plant which has been long known for exhibiting various health-beneficial effects that can largely be attributed to the polyphenolic content of the leaves. Pressurized liquid extraction (PLE) is a green extraction technique that enables the efficient isolation of polyphenols from different plant materials. Hence, the aim of this research was to determine optimal conditions for PLE (solvent, temperature, number of extraction cycles and static extraction time) of laurel leaf polyphenols and to assess the polyphenolic profile of the optimal extract by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) as well as to evaluate the antioxidant activity determined by FRAP, DPPH and ORAC assays. The optimal PLE conditions were 50% ethanol, 150 °C, one extraction cycle and 5 min static time. The polyphenolic extract obtained at optimal PLE conditions comprised 29 identified compounds, among which flavonols (rutin and quercetin-3-glucoside) were the most abundant. The results of antioxidant activity assays demonstrated that PLE is an efficient green technique for obtaining polyphenol-rich laurel leaf extracts with relatively high antioxidant activity.